2017
DOI: 10.1002/jbmr.3195
|View full text |Cite
|
Sign up to set email alerts
|

Klotho Lacks an FGF23-Independent Role in Mineral Homeostasis

Abstract: Fibroblast growth factor-23 (FGF23) is a bone-derived hormone regulating vitamin D hormone production and renal handling of minerals by signaling through an FGF receptor/aKlotho (Klotho) receptor complex. Whether Klotho has FGF23-independent effects on mineral homeostasis is a controversial issue. Here, we aimed to shed more light on this controversy by comparing male and female triple knockout mice with simultaneous deficiency in Fgf23 and Klotho and a nonfunctioning vitamin D receptor (VDR) (Fgf23/ Klotho/VD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 60 publications
1
27
0
1
Order By: Relevance
“…This leads to phosphate wasting, secondary hypophosphatemia, and low circulating 1,25(OH)2D3. This translates into hypophosphatemia and hypocalcemia or hypophosphatemic rickets in some RS patients [64,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to phosphate wasting, secondary hypophosphatemia, and low circulating 1,25(OH)2D3. This translates into hypophosphatemia and hypocalcemia or hypophosphatemic rickets in some RS patients [64,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…30,77,78,80,83 FGF23 has extrarenal effects on the cardiovascular, central nervous, and immune systems and nonrenal cells, such as MSCs and human monocytes . The main physiological function of klotho for in vivo mineral homeostasis is achieved by its role as a coreceptor mediating FGF23 action . Our new data with hMSCs showed that there was a significant correlation for constitutive expression of membrane‐bound klotho ( r = 0.52, P = 0.019) and a statistical trend of positive correlation for expression of secreted klotho ( r = 0.42, P = 0.064) with eGFR in a cohort of subjects without kidney disease .…”
Section: Impact Of Renal Function and Ckd On Vitamin D Metabolism In mentioning
confidence: 90%
“…The codependency of FGF23 and Klotho is supported by mouse genetic studies showing that Fgf23 -/and Kl -/mice are exact phenocopies, characterized by hyperphosphatemia, excess 1,25(OH) 2 D 3 , soft tissue calcifications, and early mortality (2,(27)(28)(29). The nonredundant phenotypes are further supported by the fact that Kl -/mice are refractory to FGF23 effects (30)(31)(32), and compound mutant Fgf23 and Kl have nonadditive effects (27,(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 95%